Developing Coal Bed Methane Gas Utilization Pilot Project To Produce Residential Electricity - Yusep K Caryana (Testing Center for Oil and Gas LEMIGAS, 2009)
Coal Bed Methane pilot project has produced around 80 m3 CBM gas containing around 14,66% volume of CO2 and 85,34% volume of CH4. CO2 has to be removed, the methane gas can be utilized to produce residential electricity applying the lattest technology. Some equipment need to be installed in place at proposed CBM gas site plant to produce the electricity of around 150 KWe per day or 51,75 MWe per annum from which the pilot project can be scaled up to 1 x 55 MW gas fuelled power plant.